2019
DOI: 10.33151/ajp.16.714
|View full text |Cite
|
Sign up to set email alerts
|

Exploring paramedic communication and emotional expression in the workplace after responding to emergency calls

Abstract: IntroductionParamedics are at risk of developing mental distress and disorders when exposed to traumatic calls. Several studies demonstrate that when individuals are exposed to a traumatic event, there is a correlation between a lack of social support and emotional expression, and the development of disorders such as post-traumatic stress disorder and depression. Unfortunately, little is known about the social support that paramedics receive from their peers, particularly in the workplace after respond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(24 citation statements)
references
References 46 publications
1
23
0
Order By: Relevance
“…Eight of these articles investigated communication between paramedics and a cohort of patients. These included cancer, dementia, elderly, and pediatric patients (Credland, Hurwood, & McKenzie, 2020; Drewitz‐Chesney, 2019; Noack, Kleinert, & Muller, 2020). Two articles by Ross et al (Ross, Jennings, Gosling, & Williams, 2018; Ross & Williams, 2014) investigated student paramedic communication with older patients.…”
Section: Methodsmentioning
confidence: 99%
“…Eight of these articles investigated communication between paramedics and a cohort of patients. These included cancer, dementia, elderly, and pediatric patients (Credland, Hurwood, & McKenzie, 2020; Drewitz‐Chesney, 2019; Noack, Kleinert, & Muller, 2020). Two articles by Ross et al (Ross, Jennings, Gosling, & Williams, 2018; Ross & Williams, 2014) investigated student paramedic communication with older patients.…”
Section: Methodsmentioning
confidence: 99%
“…Ten of the 24 studies included data relevant to protecting post-traumatic incident mental health,51–53 55–58 61 65 73 and one study included data relevant to barriers and facilitators for help-seeking behaviour related to mental health 72. The remaining 13 studies50 54 59 60 62–64 66–71 included data which were extracted for both of these outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…For these two mixed-methods studies, only data from sections related to their qualitative methodology were extracted. The majority of studies (16 of 24) employed a sample of ambulance personnel, [50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65] followed by police officers [66][67][68][69] and lastly firefighters. 70 71 The participants of one study, in addition to ESWs, included participants who did not match the selection criteria, 70 and two studies included a mix of different types of ESWs.…”
Section: Overview Of Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…A large volume of paramedics in this research identified pre- and post-call discussions with paramedic specialists as a critical function of their role, as well as consultations on morally and ethically complex decisions such as those at the end of life or where there is ambiguity in the most appropriate course. Paramedics have previously identified the immediate aftermath of a traumatic patient encounter as a key period in how they process and make meaning from morally and ethically challenging situations [ 26 ], with rates of PTSD in paramedics amongst the highest of any emergency service [ 27 ]. Given these consultations were not commonly reported with physician-delivered teleconsultations, it is possible these provide a key safety net for a paramedic culture fraught with traumatic stressors, as well as complex moral and ethical decisions which must be made under significant time pressures.…”
Section: Discussionmentioning
confidence: 99%